Sublingual ranula in a 71-year-old patient - Anna Janas-Naze; Adam Chiżyński; Aleksandra Szczepkowska; Piotr Osica (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2016)
The article describes a case of sublingual ranula, methods of diagnostic and treatment.